2014
DOI: 10.1016/j.enbuild.2014.04.035
|View full text |Cite
|
Sign up to set email alerts
|

The greenhouse gas emissions and mitigation options for materials used in UK construction

Abstract: The UK construction industry faces the daunting task of replacing and extending a significant proportion of UK infrastructure, meeting a growing housing shortage and retrofitting millions of homes whilst achieving greenhouse gas (GHG) emission reductions compatible with the UK's legally binding target of an 80% reduction by 2050. This paper presents a detailed time series of embodied GHG emissions from the construction sector for 1997-2011. This data is used to demonstrate that strategies which focus solely on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
79
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 144 publications
(90 citation statements)
references
References 55 publications
(78 reference statements)
1
79
0
Order By: Relevance
“…With respect to the manufacture of the materials, the use of more environmentally friendly materials obtained from renewable sources with sustainable processes could be an interesting solution for the reduction of CO2 emissions [4].…”
Section: Introductionmentioning
confidence: 99%
“…With respect to the manufacture of the materials, the use of more environmentally friendly materials obtained from renewable sources with sustainable processes could be an interesting solution for the reduction of CO2 emissions [4].…”
Section: Introductionmentioning
confidence: 99%
“…Long-term alternatives are restricted generally to very high-level forecasts, such as the Global Construction series (GCP and OE, 2013), and do not disaggregate projections beyond infrastructure, domestic and non-domestic properties. The long-term projections established for the routemap were largely based on historical trends and did not reflect current plans (Giesekam et al, 2014). Thus, as no robust, independent, disaggregated projections could be sourced, it was necessary to establish novel projections of new build.…”
Section: Future Demand Projectionsmentioning
confidence: 99%
“…The first is a time series of aggregate construction sector embodied emissions from the UK MRIO model described by Giesekam et al (2014). The second is a database of building-level LCA studies.…”
Section: The Uk Biec Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous publications on geopolymer materials investigated the effect of curing procedures, composition of the alkaline solution on strength development and hydration products, influence of temperature [18][19][20][21][22][23]. Other researchers demonstrated that geopolymer concrete is expensive comparatively with ordinary concrete [24].…”
Section: Introductionmentioning
confidence: 99%